The underground economy and tax evasion in Ghana: Implications for economic growth - Prince Amfo Wiafe; Mark Armah; Ferdinand Ahiakpor; Kwadwo Addo Tuffour (Cogent Economics & Finance, 2024)
The objective of the study was to determine the size of Ghana's "underground economy" and the extent of tax evasion in Ghana. The underground economy in most countries is vital because it serves as a survival place for most people. However, their activities are mostly related to tax evasion because their economic activities are mostly concealed from government tax authority agencies. The study used the Multiple Indicator Multiple Cause (MIMIC) model to estimate the size of Ghana's "underground economy". The data was obtained from the World Bank country indicators, Economic Freedom and Bank of Ghana and its spans from 1990 to 2020. The study is one of the premier to estimate the size of Ghana's "underground economy" using the MIMIC model. The study found that the average size of Ghana's underground economy is about 44% of the official GDP of the economy and is primarily caused by tax burden, government integrity, unemployment, government spending, self-employment, inflation and the agricultural sector employment. The estimated tax evasion due to the presence of the "underground economy" is, on average, about 6.28% of GDP. Other findings from the study were that, while tax evasion negatively affects economic growth, the underground economy's size positively affects economic growth in Ghana. We recommend that since the underground economy, to some extent, provides job security to some individuals within the country, their activities must be formalized by ensuring proper documentation and registration. Furthermore, the government should improve the ways of detecting tax evasion through intensive tax audit.
Keywords: 330; underground economy; tax evasion; economic growth; Multiple IndicatorMultiple Cause (MIMIC) model; Ghana